Bringing Real-World Microbiology Experiences to Undergraduate Students in Resource-Limited Environments - Aparna, Y.; Anuradha, K.; Jyothi, Ch.; Sri Manjari, K.; Challa, Anil Kumar (Frontiers in Microbiology, 2020)
Undergraduate microbiology curriculum should be amenable to periodic changes to incorporate new developments and ideas. The curriculum should be used not merely as a way to disseminate facts but also as a way to allow students to experience the process of science. In the context of undergraduate microbiology education in Osmania University (Hyderabad, India), existing curriculum does not explicitly allow students to engage in deeper understanding of concepts and understanding of the process of science, both in lecture and laboratory courses. The assessment methods that are currently used are limited in scope as they only test factual recall and superficial understanding of the subject and very minimally assess critical thinking skills. Another factor hampering innovation in the broader context of undergraduate education is the unavailability and inaccessibility to adequate resources. To address the issue of resource-limitations in implementing activities that expose undergraduate students to real-world microbiology experiences, a collaboration between a research institute and two teaching colleges was formed. This collaboration involved teacher and student workshops on exploring microbial diversity using 16s rRNA analysis with a view of blending novel research questions with technical skills in the undergraduate microbiology lab. This effort is an example of educators providing students with authentic experiences and, helping them gain critical knowledge and research skills in microbiology even under resource constraints, and students demonstrating motivation to participate in similar activities in the future. The collaborative effort described here can be a broadly sustainable model to improve overall undergraduate education in relatively resource-limited environments.